2021
DOI: 10.1186/s42358-021-00193-5
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis damage index in Behçet’s disease

Abstract: Background Vasculitis damage index (VDI) is a validated damage index for systemic vasculitis, and as Behçet’s disease is considered one of systemic vascular disease we aimed to study the relationship of the vasculitis damage index to clinical manifestations and comorbidity in patients with Behçet’s disease (BD) to determine if VDI could be used to assess damage in patients with BD. Methods A total of 109 patients with BD were recruited from the Rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…This can be explained by the diversity of the items scored under each organ system in each index. Regarding the vascular system, VDI includes complicated peripheral venous thrombosis (superficial varicosities, thrombophlebitis) but does not record other complicated venous occlusions such as Budd‐Chiari syndrome, cerebral venous sinus and vena cava thrombosis 8 . On the other hand, BODI includes vena cava thrombosis, pulmonary artery aneurysm and thrombosis despite excluding the pulmonary system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This can be explained by the diversity of the items scored under each organ system in each index. Regarding the vascular system, VDI includes complicated peripheral venous thrombosis (superficial varicosities, thrombophlebitis) but does not record other complicated venous occlusions such as Budd‐Chiari syndrome, cerebral venous sinus and vena cava thrombosis 8 . On the other hand, BODI includes vena cava thrombosis, pulmonary artery aneurysm and thrombosis despite excluding the pulmonary system.…”
Section: Discussionmentioning
confidence: 99%
“…18 This agreed with previous reports of Piga et al and Elgengehy et al who found that mucocutaneous damage and ocular damage were the most common. 8,9 On the other hand, Suppiah et al stated that ENT and neuropsychiatric systems had the most frequent organ damage as determined by VDI. 17 correlation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular involvement in BD may also play a role in progression of ON, however, there is not enough evidence to support this hypothesis [ 21 ]. In the study by Elgengehy et al Vasculitis damage index in BD patients is significantly associated with ON [ 22 ]. Vascular damage and impaired endothelial dysfunction play different role in development of ON [ 23 ].…”
Section: Discussionmentioning
confidence: 99%